Recruitment in Britain: examining employers' practices and attitudes to employing UK-born and foreign-born workers - Broughton, Andrea; Adams, Lorna; Cranney, Marc; Dobie, Sarah; Marangozov, Rachel; Markaki, Yvonni; Sumption, Madeleine (London, 2016)
"Report looking at the results of research into employer and employee practices, perceptions and experiences of recruitment. Our aim was to understand whether there was any evidence of different treatment between UK-born and foreign-born workers with a right to work in the UK, the extent of discrimination on the basis of nationality, and what may be causing it."